Bunnybear - Loney, Andrea J. (Albert Whitman & Company, 2017)
"Although Bunnybear was born a bear, he feels more like a bunny. He loves to bounce through the forest, wiggle his nose, and munch on strawberries. The other bears don't understand him, and neither do the bunnies. Will Bunnybear ever find a friend who likes him just the way he is?"--